Control of a quadcopter - Mohd Iqbal, Mustaparudin (2016)
This thesis is about the development of a quadcopter project from the modelling and simulation to the construction of the real testbed. Objective of this project is to evaluate the reliability of the mathematical model of the quadcopter on the real platform, mainly for when performing hover. For the modelling part of this thesis it discusses the application of Euler-Newton method and how the simulation in MATLAB Simulink is built based on the equations derived from it. Analysis of the simulation includes comparison of different values of tuning gain together with their effect on the performance of the quadcopter. Then a real quadcopter is built from scratch as a prototype model to test the controller obtained from the simulation.